1, 3-Butadiene-induced mitochondrial dysfunction is correlated with mitochondrial CYP2E1 activity in Collaborative Cross mice. (1st March 2017) - Hartman, Jessica H.; Miller, Grover P.; Caro, Andres A.; Byrum, Stephanie D.; Orr, Lisa M.; Mackintosh, Samuel G.; Tackett, Alan J.; MacMillan-Crow, Lee Ann; Hallberg, Lance M.; Ameredes, Bill T.; Boysen, Gunnar
Abstract: Cytochrome P450 2E1 (CYP2E1) metabolizes low molecular weight hydrophobic compounds, including 1, 3-butadiene, which is converted by CYP2E1 to electrophilic epoxide metabolites that covalently modify cellular proteins and DNA. Previous CYP2E1 studies have mainly focused on the enzyme localized in the endoplasmic reticulum (erCYP2E1); however, active CYP2E1 has also been found in mitochondria (mtCYP2E1) and the distribution of CYP2E1 between organelles can influence an individual's response to exposure. Relatively few studies have focused on the contribution of mtCYP2E1 to activation of chemical toxicants. We hypothesized that CYP2E1 bioactivation of 1, 3-butadiene within mitochondria adversely affects mitochondrial respiratory complexes I–IV. A population of Collaborative Cross mice was exposed to air (control) or 200ppm 1, 3-butadiene. Subcellular fractions (mitochondria, DNA, and microsomes) were collected from frozen livers and CYP2E1 activity was measured in microsomes and mitochondria. Individual activities of mitochondrial respiratory complexes I–IV were measured using in vitro assays and purified mitochondrial fractions. In air- and 1, 3-butadiene-exposed mouse samples, mtDNA copy numbers were assessed by RT-PCR, and mtDNA integrity was assessed through a PCR-based assay. No significant changes in mtDNA copy number or integrity were observed; however, there was a decrease in overall activity of mitochondrial respiratory complexes I, II, and IV after 1, 3-butadiene exposure. Additionally, higher mtCYP2E1 (but not erCYP2E1) activity was correlated with decreased mitochondrial respiratory complex activity (in complexes I–IV) in the 1, 3-butadiene-exposed (not control) animals. Together, these results represent the first in vivo link between mitochondrial CYP2E1 activity and mitochondrial toxicity.